HDL in innate and adaptive immunity - Catapano, A.; Pirillo, A.; Bonacina, F.; Norata, Giuseppe (2014)
During infections or acute conditions high-density lipoproteins cholesterol (HDL-C) levels decrease very rapidly and HDL particles undergo profound changes in their composition and function. These changes are associated with poor prognosis following endotoxemia or sepsis and data from genetically modified animal models support a protective role for HDL. The same is true for some parasitic infections, where the key player appears to be a specific and minor component of HDL, namely apoL-1. The ability of HDL to influence cholesterol availability in lipid rafts in immune cells results in the modulation of toll-like receptors, MHC-II complex, as well as B- and T-cell receptors, while specific molecules shuttled by HDL such as sphingosine-1-phosphate (S1P) contribute to immune cells trafficking. Animal models with defects associated with HDL metabolism and/or influencing cell cholesterol efflux present features related to immune disorders. All these functions point to HDL as a platform integrating innate and adaptive immunity. The aim of this review is to provide an overview of the connection between HDL and immunity in atherosclerosis and beyond. © The Author 2014.